[PP.12.01] BLOOD PRESSURE CONTROL IN PATIENTS WITH ESSENTIAL AND RENOPARENCHYMAL ARTERIAL HYPERTENSION. (September 2017) - Radchenko, G.; Salascheva, T.; Sirenko, Y.
Abstract : Objective: The aim of study was to compare blood pressure (BP) control in Ukrainian population with renoparenchymal (RAH) and essential arterial hypertension (AH) and define the factors associated with failed BP control during 3-month therapy. Design and method: 9259 patients with BP > 140/90 mmHg were included in 3-month multicentre open trial. All patients were divided in 2 groups: 1st–2197 (23.7%) patients with RAH; 2nd −7062 (76.3%) with essential AH. Patients were treated by primary care physicians. On 4 visits were done: office BP measurements, ECG, patient's compliance and cardiovascular risk evaluations by standard tests, inquiring by author's questionnaire. Multifactor regression analysis was used for evaluation of antihypertensive treatment failure predictors. Results: Patients with RAH had more complications, concomitant diseases, risk factors and target organ damage (left ventricular hypertrophy, renal dysfunction). The target BP was achieved in 53.9% patients of 1st group and in 60.7% (p < 0.001) of 2nd group. The mean quantity of antihypertensive drugs and combination therapy rate were more in 1st group −2.2 ± 0.02 vs 2.04 ± 0.01 (p < 0.001) and 64 vs 57.1% (p < 0.001). Baseline in both groups only small part of patients had high treatment compliance–20.1% and 23.5% in 1st and 2nd groups (p < 0.001). We noted improvement in patient compliance in both groups on treatment, but more rate of low complained patients was in 1st group than in 2nd at the end. In both groups poor BP control was associated with baseline systolic and diastolic BP level. Higher patient compliance at the end (but not baseline) and fruit/vegetable consumption decreased the chance of failed BP control in both groups. In patients with RAH more age and quantity of antihypertensive drugs were associated with poor BP control, while additional physical activity- with success in treatment. Heart failure and history of myocardial infarction increased and high education level of patients/"working" status decreased the chance of poor BP control only in 2nd group. Conclusions: Patients with RAH had more complications and needed more attention and aggressive BP management with other risk factor corrections. We need to use defined common and different factors associated with poor BP control for more effective antihypertensive treatment of patients with different etiology of hypertension.